ANALISIS TARIF ANGKUTAN UMUM BERDASARKAN BIAYA OPERASIONAL KENDARAAN DI KOTA AMBON (STUDI KASUS KONDISI PSBB) - Fuad Hasan Ohorella; Imran Oppier (Fakultas Teknik Universitas Pattimura, 2021)
Public transportation between the island seas is one of the economic backbones where Maluku Province is an archipelagic area. Ambon City as the capital of Maluku Province is a city with activities and interactions between communities using public transportation to support daily activities. However, due to the enactment of PSBB (Large-Scale Social Restrictions) from June 23 to November 22, 2020, the number of public transportations (Perwali No. 18) is limited, with odd-even implementations up to passenger restrictions (6 people per trip), resulting in operational costs. Vehicles will increase. This study aims to find out how much the upper and lower limit tariffs are used for the community and students. In this study, the calculation method was used according to the Standards of the Directorate General of Land Transportation (2002) SK 687/AJ.206/DRDJ/2002. The results of the study show that the upper and lower tariff rates for the community in Nusaniwe District are Rp. 16,592 – Rp. 11,061,-; Sirimau District IDR 5,138 – IDR 3,425,-; and Baguala and Teluk Ambon Districts Rp. 25,000 – Rp. 16,666,-. The upper and lower limit rates for students in Nusaniwe District are Rp. 8,296 – Rp. 5,531,-; Sirimau District IDR 2,569 – IDR 1,712,-; and Baguala and Teluk Ambon Districts Rp 12,500 – Rp 8,333,-. Tariffs based on the BOK during the PSBB period ranged from Rp. 25,000 – Rp. 5,138,-, while the real tariff was Rp. 3,000 – Rp. 5,000.